2019
DOI: 10.1002/htj.21580
|View full text |Cite
|
Sign up to set email alerts
|

Effect of heat source/sink on MHD flow due to porous rotating disk with variable thickness in the presence of cross diffusion

Abstract: An analysis of steady magnetohydrodynamic axisymmetric flow of a viscous incompressible electrically conducting fluid due to porous rotating disk with variable thickness in the presence of heat source/sink is presented. Soret and Dufour effects (cross-diffusion) are also considered. The governing partial differential equations are transformed into a system of nonlinear ordinary differential equations. The homotopy analysis method is used to solve the resulting coupled nonlinear equations under appropriate tran… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 25 publications
0
2
0
Order By: Relevance
“…Ever since, HAM has been successfully used, literally in hundreds of papers, for the study of boundary layer flows. Indicatively, it is mentioned that recently HAM has been used for the study of flows of nanofluids [24,[50][51][52][53][54][55] and flows in porous media [56][57][58][59].…”
Section: Introductionmentioning
confidence: 99%
“…Ever since, HAM has been successfully used, literally in hundreds of papers, for the study of boundary layer flows. Indicatively, it is mentioned that recently HAM has been used for the study of flows of nanofluids [24,[50][51][52][53][54][55] and flows in porous media [56][57][58][59].…”
Section: Introductionmentioning
confidence: 99%
“…Shemshuddin et al, 3 Sajjad et al, 4 and Sravanthi 5 investigated the impact of the magnetic field on micropolar fluid induced along a stretching surface, including heat source/sink and on the similar flow of a micropolar fluid between two disks accordingly. It is observed that the microrotation profile shows improving performance with the magnetic field in the presence of heat source/sink while it reveals the opposite performance in the absence of heat source/sink.…”
Section: Introductionmentioning
confidence: 99%